Evolution and changes in the physician-patient relationship (Colombia Medica, 2024)
The idealized vision of the physician-patient relationship was characterized by patient trust and physician availability, in a long-term relationship in which physicians knew many things about their patients and their families, being the physician a part of the patient's community. Physician employers, pharmaceutical companies, and insurance companies have abruptly entered the once private relationship between physicians and patients, changing a true relationship into a simple encounter. The substitution of the generic terms physician and patient for provider and client mirrors the increased impersonality of the encounter based on the commercialization of medicine. The present review analyzes the situations, which have led to the progressive and unavoidable deterioration of the physician-patient relationship within a globalized society.